Pendampingan digitalisasi UMKM Toko batik pertiwi : Inovasi Pengabdian masyarakat untuk Transormasi Bisnis - Nur Fitriana; Yohana Simanjuntak; Nadia Vega; Hani Eka; Handra Iqlima; Yuda lia; Aprilia Zuldewari (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
This study aims to examine the impact of digital transformation assistance on the Toko Batik Pertiwi MSME, located in Jalan Jenderal Sudirman, Pekanbaru, Riau. The business faced challenges in managing financial records manually and had not yet optimized the use of digital media for product promotion. These issues limited financial evaluation and narrowed market reach. The community service was carried out using a qualitative approach through stages including field studies, in-depth interviews, system analysis, digital solution design, training, and effectiveness evaluation. The assistance program included implementing the Buku Warung application for daily financial record-keeping, creating social media accounts such as Instagram, Facebook Place, and WhatsApp Business, as well as content creation and logo design for brand identity. The results showed significant improvements in financial management, increased online visibility, and stronger brand recognition. The business owner adapted well to digital tools and demonstrated increased self- confidence in managing the business digitally. This program positively impacted operational efficiency, market expansion, and improved digital literacy for MSME actors.